1998
DOI: 10.1083/jcb.143.5.1155
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Fusion Mediated by Baculovirus gp64 Involves Assembly of Stable gp64 Trimers into Multiprotein Aggregates

Abstract: The baculovirus fusogenic activity depends on the low pH conformation of virally-encoded trimeric glycoprotein, gp64. We used two experimental approaches to investigate whether monomers, trimers, and/or higher order oligomers are functionally involved in gp64 fusion machine. First, dithiothreitol (DTT)- based reduction of intersubunit disulfides was found to reversibly inhibit fusion, as assayed by fluorescent probe redistribution between gp64-expressing and target cells (i.e., erythrocytes or Sf9 cells). This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 45 publications
4
66
2
Order By: Relevance
“…The hemagglutinin fusion protein of influenza is proposed to function as a trimer (16). The gp64 viral fusion protein of baculovirus also oligomerizes into multimers to mediate fusion (17). Although it has been suggested that SNARE complexes may form a ring around the fusion site, there are little or no data in support of this hypothesis.…”
mentioning
confidence: 50%
“…The hemagglutinin fusion protein of influenza is proposed to function as a trimer (16). The gp64 viral fusion protein of baculovirus also oligomerizes into multimers to mediate fusion (17). Although it has been suggested that SNARE complexes may form a ring around the fusion site, there are little or no data in support of this hypothesis.…”
mentioning
confidence: 50%
“…Electrophysiological experiments on baculovirus-infected Sf9 cells led Plonsky and Zimmerberg (1996) to propose that a ring of five to seven GP64 trimers may form a fusion machine that facilitates opening of the fusion pore within this ring. Furthermore, using polypeptide cross-linking agents and sulfhydryl group reagents, Markovic et al (1998) demonstrated that GP64 forms transient, higher-order complexes of trimers upon application of low pH buffer (only in the presence of target membrane) at the same time that fusion is catalyzed. The ring hypothesis is further supported by work with influenza HA, which suggests that HA trimers function cooperatively and inhibit lipid dye transmigration during the initial fusion phases (Ellens et al, 1990;Clague et al, 1991;Tse et al, 1993;Zimmerberg et al, 1994;Blumenthal et al, 1996;Danieli et al, 1996;Chernomordik et al, 1998).…”
Section: The Mechanism Of Membrane Fusionmentioning
confidence: 99%
“…These transient ring structures are proposed to facilitate conversion of kinetic energy, released during protein conformational change, into work on the target and host membranes required for membrane fusion. Indeed, biochemical evidence for baculovirus GP64 aggregates during membrane fusion has recently been reported (Markovic et al 1998). Whether and how viral fusion proteins might function in a coordinated and cooperative manner is a major question in the field of membrane fusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gp64 fusion protein of baculovirus has intermolecular disulfide bonds linking the three subunits of a trimer. Reduction of these bonds with DTT inhibits membrane fusion and prevents gp64 from assembling into a higher order fusion complex (23). Disulfide bonds within the human immunodeficiency virus fusion protein must be rearranged by protein disulfide isomerase isoforms present on the cell surface to permit a conformational shift required for membrane merger (24 -26).…”
Section: Discussionmentioning
confidence: 99%